Curriculum Development in the Field of Information Science: Knowledge organization Courses - Lasić-Lazić, Jadranka (Array, 2003)
This paper will examine new curriculum developments in the Department of Information Sciences at the University of Zagreb. The TEMPUS project offers the opportunity for planned and organized efforts for curriculum change in courses within the field of knowledge organization. This paper explains the main rationale and need for these changes as well as steps that have already been planned and undertaken. The objective of these changes is to improve course organization and coherence and modular flexibility throughout different programmes in the Department. During the first year of the TEMPUS project the focus was on rethinking and modernizing course content. This was achieved through analysis of knowledge organization course syllabi worldwide and through organized visits to two universities in the United Kingdom. This paper will shed some light on new and common subject areas within the field of knowledge organization, and the rationale behind including new topics in existing modules.